mTOR-related linc-PMB promotes mitochondrial biogenesis via stabilizing SIRT1 mRNA through binding to the HuR protein - Chen Qian; Zhang Huaying; Wang Daokun; Liao Wenjing; Liu Yazhou; Cai Yurui; Wang Siyou; Yu Mengqian (Acta Biochimica et Biophysica Sinica)
Mitochondrial dysfunction is implicated in numerous disorders, including type 2 diabetes, Alzheimer’s disease and cancer. Long non-coding RNAs (lncRNAs) are emerging as pivotal regulators of cellular energy metabolism, yet their roles remain largely unclear. In this study, we identify an lncRNA named linc-PMB, which is associated with mTOR and promotes mitochondrial biogenesis, through microarray analysis. We demonstrate that the knockdown of linc-PMB results in significantly impaired mitochondrial respiration and biogenesis, along with altered expressions of related genes. Conversely, overexpression of linc-PMB markedly increases mitochondrial function. We further reveal that linc-PMB interacts with the RNA-binding protein HuR, promoting the stabilization of SIRT1 mRNA and a substantial increase in SIRT1 expression, which in turn activates the PGC-1α/mtTFA pathway and mitochondrial biogenesis. Collectively, our findings reveal a novel regulatory pathway in which linc-PMB, through its interaction with HuR, modulates the SIRT1/PGC-1α/mtTFA axis to maintain mitochondrial biogenesis and function.